Potential use of TIA-1, MFF, microRNA-200a-3p, and microRNA-27 as a novel marker for hepatocellular carcinoma - Tak, Hyosun; Kang, Hoin; Ji, Eunbyul; Hong, Youlim; Kim, Wook; Lee, Eun Kyung (Biochemical and Biophysical Research Communications, 2018)
Precise and early diagnosis is critical to improve the survival rate of hepatocellular carcinoma (HCC) patients. Although several genetic and protein markers have been developed and are currently used for diagnosis, prognosis, risk stratification, and therapeutic monitoring, application of these markers still needs to be improved for better specificity and efficacy. In this study, we investigated the relative expression of mitochondrial dynamics-regulating factors including T-cell intercellular antigen protein-1 (TIA-1), mitochondrial fission factor (MFF), microRNA (miR)-200a-3p, and miR-27a/b in the liver tissues from HCC patients. The expressions of TIA-1 and MFF were augmented in the cancerous liver tissues compared to the corresponding non-tumor tissues at mRNA and protein level, while the levels of miR-200a-3p and miR-27a/b were relatively lower in the cancerous liver tissues. In addition, high levels of TIA-1 and MFF mRNA were related to the poor survival rate of HCC patients. Our results indicated that the expressions of TIA-1, MFF, miR-200a-3p, and miR-27a/b in the cancerous liver tissues differed to these in non-cancerous tissues of HCC patients, demonstrating that these gene expressions could be potential markers for the diagnosis and prognosis of HCC.
Keywords: Biomarkers; Carcinoma, Hepatocellular; Gene Expression Regulation, Neoplastic; Humans; Liver; Liver Neoplasms; Membrane Proteins; MicroRNAs; Mitochondrial Proteins; Survival Rate; T-Cell Intracellular Antigen-1; Hepatocellular carcinoma; MFF; microRNAs; TIA-1